Effect of an intervention for patients 65 years and older with blunt chest injury: Patient and health service outcomes. Issue 9 (September 2022) - Curtis, Kate; Kourouche, Sarah; Asha, Stephen; Buckley, Thomas; Considine, Julie; Middleton, Sandy; Mitchell, Rebecca; Munroe, Belinda; Shaban, Ramon Z.; Lam, Mary; Fry, Margaret
Highlights: Blunt chest injury has significant health consequences for older adults. Implementation of a blunt chest injury care bundle improved health care delivery, particularly appropriate analgesia, respiratory support and clinician engagement The blunt chest injury care bundle resulted in reduced unplanned ICU admissions and NIV use for older adults. Abstract: Introduction: Blunt chest injury in older adults, aged 65 years and older, leads to significant morbidity and mortality. The aim of this study was to evaluate the effect of a multidisciplinary chest injury care bundle (ChIP) on patient and health service outcomes in older adults with blunt chest injury. Methods: ChIP comprised multidimensional implementation guidance in three key pillars of care for blunt chest injury: respiratory support, analgesia, and complication prevention. Implementation was guided using the Behaviour Change Wheel. This proof-of-concept controlled pre- and post-test study with two intervention and two control sites in Australia was conducted from July 2015 to June 2019. The primary outcomes were non-invasive ventilation (NIV) use, unplanned Intensive Care Unit (ICU) admissions, and in-hospital mortality. Secondary outcomes were health service and costing outcomes. Results: There were 1122 patients included in the analysis, with 673 at intervention sites (331 pre-test and 342 post-test) and 449 at control sites (256 pre-test and 193 post-test). ChIP was associated with unplanned ICU admissions and in NIV use with a reduction of the odds in the post vs the pre periods in the intervention sites when compared to the controls (ratio of OR=0.13, 95%CI=0.03-0.55) and (ratio of OR=0.14, 95%CI=0.02-0.98) respectively. There was no significant change in mortality. Implementing ChIP was also associated with health service team reviews with an increased odds in the post vs pre periods in the intervention sites in comparison to the controls for surgical review (ratio of OR =6.93, 95%CI=4.70-10.28), ICU doctor (ratio of OR =5.06, 95%CI=2.26-9.25), ICU liaison (ratio of OR =14.14, 95%CI=3.15-63.31), and pain (ratio of OR =5.59, 95%CI=3.25-9.29). ChIP was also related to incentive spirometry (ratio of OR=6.35, 95%CI= 3.15-12.82) and overall costs (ratio of mean ratio=1.34, 95%CI=1.09-1.66) with a higher ratio for intervention sites. Conclusion: Implementation of ChIP using the Behaviour Change Wheel was associated with reduced unplanned ICU admissions and NIV use and improved health care delivery. Trial registration: ANZCTR: ACTRN12618001548224, approved 17/09/2018